Circulating Autoantibodies Targeting TREK-1 in Patients With Short-Coupled Ventricular Fibrillation - Li, Jin; Janin, Alexandre; Patoughi, Mona; Gaudreault, Nathalie; Kis, Lenke; Moha Ou Maati, Hamid; Bossé, Yohan; Steinberg, Christian (Circulation (New York, N.Y.), 2024)
BACKGROUND: Short-coupled ventricular fibrillation (SCVF) is increasingly being recognized as a distinct primary electrical disorder and cause of otherwise unexplained cardiac arrest. However, the pathophysiology of SCVF remains largely elusive. Despite extensive genetic screening, there is no convincing evidence of a robust monogenic disease gene, thus raising the speculations for alternative pathogeneses. The role of autoimmune mechanisms in SCVF has not been investigated so far. The objective of this study was to screen for circulating autoantibodies in patients with SCVF and assess their role in arrhythmogenesis. METHODS: This is a prospective, single-center, case-control study enrolling cardiac arrest survivors diagnosed with SCVF or idiopathic ventricular fibrillation (IVF) between 2019 and 2023 at the Institut Universitaire de Cardiologie et de Pneumologie de Québec, Université Laval Inherited Arrhythmia Clinic in Canada. Plasma samples were screened for autoantibodies targeting cardiac ion channels using peptide microarray technology. Identified target autoantibodies were then purified from pooled plasma samples for subsequent cellular electrophysiological studies. RESULTS: Fourteen patients with SCVF (n=4 [29% of patients] female patients; median age, 45 years [interquartile range: 36, 59]; n=14 [100% of patients] non-Hispanic White) and 19 patients with idiopathic ventricular fibrillation (n=8 [42%] female patients; median age, 49 years [38, 57]; n=19 [100%] non-Hispanic White) were enrolled in the study and compared with 38 (n=20 [53%] female subjects; median age, 45 years [29, 66]; n=36 [95%] non-Hispanic White) sex-, age- and ethnicity-matched healthy controls. During the study period, 11 (79%) SCVF probands experienced ventricular fibrillation recurrence after a median of 4.3 months (interquartile range, 0.3-20.7). Autoantibodies targeting cardiac TREK-1 (TWIK [tandem of pore-domains in a weakly inward rectifying potassium channel]-related potassium channel 1 were identified in 7 (50%) patients with SCVF (P=0.049). Patch clamp experiments demonstrated channel-activating properties of anti-TREK-1 autoantibodies that are antagonized by quinidine in both HEK293 cells and human induced pluripotent stem cell-derived cardiomyocytes. CONCLUSIONS: Patients with SCVF harbor circulating autoantibodies against the cardiac TREK-1 channel. Anti-TREK-1 autoantibodies not only present the first reported biomarker for SCVF, but our functional studies also suggest a direct implication in the arrhythmogenesis of SCVF.